The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/emermed-2020-210999
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rib fractures: does flail chest matter?

Abstract: BackgroundRecent studies have reported significant morbidity and mortality in patients with multiple rib fractures, even without flail chest. The aim of this study was to compare the clinical outcome and incidence of associated chest injuries between patients with and without flail chest, with three or more rib fractures.MethodsThis study included patients with blunt trauma with at least three rib fractures, hospitalised during 2010–2019 in the Hillel Yaffe Medical Center in central Israel (level II trauma cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…In contrast to our study results, other studies have already indicated respiratory failure as being more likely associated with the underlying lung injury rather than chest wall motion mechanics 15 , 30 32 , since Trinkle et al’s study 50 years ago 33 . In this prospective study conducted with 30 patients with flail chest, the authors concluded that the role of flail motion was minor.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study results, other studies have already indicated respiratory failure as being more likely associated with the underlying lung injury rather than chest wall motion mechanics 15 , 30 32 , since Trinkle et al’s study 50 years ago 33 . In this prospective study conducted with 30 patients with flail chest, the authors concluded that the role of flail motion was minor.…”
Section: Discussioncontrasting
confidence: 99%
“…Respiratory failure by muscle fatigue can even occur several days after the initial trauma 11 14 . Several recent studies have also concluded that the presence of the flail chest does not affect adverse outcomes 15 , 32 . However, these two studies were conducted without distinction between the anatomic flail segment and the paradoxical chest wall movement.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, recent nationwide studies by Peek et al [29] and Kishawi et al [30] reported mortality rates of 2.1-2.5% among patients with isolated rib fractures with HLOS, LOS, and DOV similar to those observed in our study [29]. Furthermore, newer studies are indicating that NRF is not associated with worst mortality, HLOS, ICU-LOS, or days on mechanical ventilation [31][32], unlike those of Bulger et al [3], Stawicki et al [25], and Pape et al [26]. Their studies all noted a positive association between NRF and mortality.…”
Section: Discussionsupporting
confidence: 86%
“…Despite their efficacy, these methods may result in substantial muscle disruption and subsequent permanent disability of the affected limb. 31 In this research, we conducted the comparative analysis of the outcomes linked to two types of rib fracture fixation techniques: EF utilizing a thoracic girdle and internal fixation utilizing the auscultatory triangle method. Various factors were evaluated, such as the overall patient prognosis, secondary trauma and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional surgical techniques, including longitudinal, posterior or anterior incisions, have been the norm. Despite their efficacy, these methods may result in substantial muscle disruption and subsequent permanent disability of the affected limb 31 …”
Section: Discussionmentioning
confidence: 99%